Przyczynek do identyfikacji średniowiecznej aparatury destylacyjnej w Polsce - Szymański, Michał (Acta Universitatis Lodziensis. Folia Archaeologica, 2017)
Although alembics, erstwhile distilling-apparatus, are deeply rooted in Polish traditional culture, they have not been yet analysed separately. Ceramic and glass alembics, rarely being discovered during excavations within Poland, are also seldom published. Therefore using Western European studies seems to be necessary to amend that state of being. The case study on distilling-apparatus from France and Great Britain, which was used in the article, has been compiled by S. Moorhouse and N. Thomas. They presented morphologic traits of the devices: vaporizer – distilling-base or cucurbit used for heating the raw material, and alembic – a still-head with collecting-channel and spout. The authors also described industrial, kitchen and alchemical use of the devices. Based on the morphological traits, 3 types of ceramic and glass alembics were established, and presented in the article. Article uses findings already published, focuses on preliminary issues and is an attempt on introducing the reader to the matter of former distilling-apparatus. Amongst sources published in Poland one should distinguish graphics from Marcin Siennik’s Herbarz, to iest ziół tutecznych y zamorskich opisanie, Polish 16th century herbarium, fragments of pottery distilling-base from the knight’s stronghold from Mymoń, Podkarpackie Voivodeship and alembic from castle in Puck, Pomeranian Voivodeship. The latter, although ceramic, represents advanced type of distilling-apparatus with an external cooling system – removable pipe, placed in the barrel with water. Amongst instalations associated with alembics, one should mention special furnaces (athanors), ember dispensers and receivers for distillate. Another fact worth mentioning is that distilling-apparatus could be luted with a special alchemical clay, recipe of which is known from Renaissance herbarium by Marcin Siennik. Alchemical utensils were frequently placed in a separate room, especially in pharmacies and distilleries. Distilling-apparatus, artefacts heretofore neglected in Poland, could help in development of studies in the history of chemistry and complement an image of cultural space in pre-industrial Central Europe.